PERANCANGAN SISTEM INFORMASI PELAYANAN ADMINISTRASI DESA SUKASARI BERBASIS WEB - Ratih Dwi Asworowati; Natong, Asriani; Azizah, Ayu; Komalasari , Yuli; Nurrahman, Dede; Nuristi Qomah, Erma (LP2M Institut Informatika Dan Bisnis Darmajaya, 2024)
The existing system at Sukasari Village Office is manual, starting from the collection of population information to archiving other data related to government service processes and report generation. Therefore, recording errors and inaccurate reports may occur during the process, and it takes too long to find the required data. This system design is the right solution to solve the problems in this village government. The research methods used are data collection methods, namely observation and interviews, software development methods, namely Needs Analysis, System and Software Design, Implementation and Unit Testing, and literature study methods. Research shows that services to the community are less than optimal because the system has not been computerised. Therefore, the authors designed a web-based administrative service information system as a solution to the problems of the Sukasari village office. The results of the research are the design of the web-based Sukasari Village administration service information system. Keywords : Design; Information; Systems Services; Village; Administration.